2011
DOI: 10.1002/mnfr.201100291
|View full text |Cite
|
Sign up to set email alerts
|

Integrative metabolome and transcriptome profiling reveals discordant energetic stress between mouse strains with differential sensitivity to acrolein‐induced acute lung injury

Abstract: A respiratory irritant, acrolein is generated by overheating cooking oils or by domestic cooking using biomass fuels, and is in tobacco smoke, an occupational health hazard in the restaurant workplace. To better understand the metabolic role of the lung and to generate insights into the pathogenesis of acrolein-induced acute lung injury, SM/J (sensitive) and 129×1/SvJ (resistant) inbred mouse strains were exposed and the lung metabolome was integrated with the transcriptome profile. A total of 280 small molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
(59 reference statements)
0
24
1
Order By: Relevance
“…In a process that consumes 40% of a cell's energy, Na,K-ATPase maintains the sodium-potassium electrochemical gradient across the plasma membrane by exporting three Na 1 and importing two K 1 for each ATP hydrolyzed (77). In previous metabolomics analyses of acrolein-and chlorine-induced lung injury, we observed that the lung undergoes energetic stress and that resistant mice appear better able to use substrates for energy production (33,34). The Na,K-ATPase-generated electrochemical gradient is essential for edema fluid absorption from the alveolus (1, 3).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In a process that consumes 40% of a cell's energy, Na,K-ATPase maintains the sodium-potassium electrochemical gradient across the plasma membrane by exporting three Na 1 and importing two K 1 for each ATP hydrolyzed (77). In previous metabolomics analyses of acrolein-and chlorine-induced lung injury, we observed that the lung undergoes energetic stress and that resistant mice appear better able to use substrates for energy production (33,34). The Na,K-ATPase-generated electrochemical gradient is essential for edema fluid absorption from the alveolus (1, 3).…”
Section: Discussionmentioning
confidence: 67%
“…The genetic and transcriptomic findings here may be limited to this compound and thus may not be relevant to other forms of ALI. We previously identified candidate genes associated with acrolein-induced (32,33) and chlorine-induced ALI (34), and these genes differed from those identified with phosgene. Until several types of chemically induced ALI have been evaluated, generalizations to other forms may not be warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microarrays (n ¼ 5 mice/strain/time) and quantitative RT-PCR (n ¼ 8 mice/strain/time) were used to contrast transcript levels of candidate genes. Metabolomic profiling was performed as described previously (60)(61)(62)(63), using lung tissue (n ¼ 5 mice/strain/time) that was homogenized in deionized water containing recovery standards, extracted (80:20 methanol/water), and analyzed by positive or negative ultrahigh performance liquid chromatography-mass spectrometry/mass spectrometry (LC:Surveyor; ThermoFisher, Pittsburgh, PA) (61), or by gas chromatography-mass spectrometry (ThermoFinnegan Mat-95XP; ThermoFisher) (61). In contrast to the accuratemass and elution-time tags used in shotgun proteomics, our library-based approach combines accurate retention times and tandem mass spectrometric fragmentation patterns to unambiguously identify .2,400 biochemicals (63).…”
Section: Methodsmentioning
confidence: 99%